Exome-Sequencing Identifies Novel Genes Associated with Recurrent Pregnancy Loss in a Chinese Cohort - Xiang, Huifen; Wang, Chunyan; Pan, Hong; Hu, Qian; Wang, Ruyi; Xu, Zuying; Li, Tengyan; Su, Yezhou; Ma, Xu; Cao, Yunxia; Wang, Binbin (Frontiers in Genetics, 2021)
Recurrent pregnancy loss (RPL) is a common reproductive problem affecting around 5% of couples worldwide. At present, about half of RPL cases remained unexplained. Previous studies have suggested an important role for genetic determinants in the etiology of RPL. Here, we performed whole-exome sequencing (WES) analysis on 100 unrelated Han Chinese women with a history of two or more spontaneous abortions. We identified 6736 rare deleterious nonsynonymous variants across all patients. To focus on possible candidate genes, we generated a list of 95 highly relevant genes that were functionally associated with miscarriage according to human and mouse model studies, and found 35 heterozygous variants of 28 RPL-associated genes in 32 patients. Four genes (FOXA2, FGA, F13A1, and KHDC3L) were identified as being strong candidates. The FOXA2 nonsense variant was for the first time reported here in women with RPL. FOXA2 knockdown in HEK-293T cells significantly diminished the mRNA and protein expression levels of LIF, a pivotal factor for maternal receptivity and blastocyst implantation. The other genes, with 29 variants, were involved in angiogenesis, the immune response and inflammation, cell growth and proliferation, which are functionally important processes for implantation and pregnancy. Our study identified several potential causal genetic variants in women with RPL by WES, highlighting the important role of genes controlling coagulation, confirming the pathogenic role of KHDC3L and identifying FOXA2 as a newly identified causal gene in women with RPL.